A Debris Clearance Robot for Extreme Environments - West, Craig; Arvin, Farshad; Cheah, Wei; West, Andrew; Watson, Simon; Giuliani, Manuel; Lennox, Barry (Lecture notes in computer science, 2019)
The need for nuclear decommissioning is increasing globally, as power stations and other facilities utilising nuclear reaches the end of their operational life. Currently the majority of decommissioning tasks are carried out by workers in protective air fed suits, which is slow, expensive and dangerous. The work presented here is the early stages in the development of a flexible mobile manipulator platform, combining a Clearpath Husky, a Universal UR5 manipulator and various sensors. The system will be used for research specifically in the area of exploration of contaminated environments, map building to aid in task planning, and also to investigate manipulation for waste sorting. The aim is to develop a system that can, in the short term, be used in real world tasks but longer term function as a research platform to allow continued research and development. As well as developing a hardware platform, a detailed simulation model is also being developed to allow testing of algorithms in simulation before being deployed on hardware. The use of the simulation model for operator training is also an area that will be investigated in the future. This article focuses on the planned work for developing the system, as well as discussing the progress on the simulation model.